Synthetic approaches to metal-coordination-directed macrocyclic complexes - Fang, Qingqing; Xu, Yan; Yan, Xiaosheng; Jiang, Tao; Jiang, Yunbao (Frontiers in Chemistry, 2022)
Metal-coordination-directed macrocyclic complexes, in which macrocyclic architectures are formed by metal-ligand coordination interactions, have emerged as attractive supramolecular scaffolds for the creation of materials for applications in biosensing and therapeutics. Despite recent progress, uncontrolled multicyclic cages and linear oligomers/polymers is the most likely outcome from metal-ligands assembly, representing a challenge to current synthetic methods. Herein we outlined the state-of-art synthetic approaches to the metal-coordination-directed macrocyclic complexes by using foldable ligands or through assembly of amphiphilic ligands. This mini-review offers a guideline for the efficient preparation of metal-coordination-directed macrocyclic complexes with predictable and controllable structures, which may find applications in many biology-related areas.